A sensorless efficiency-optimizing vector control scheme for an induction motor drive - Balogun, Adeola; Olajube, Ayobami; Awelewa, Ayokunle; Okafor, Frank; Sanni, Timilehin; Samuel, Isaac (Frontiers in Energy Research, 2024)
In this paper, an energy-saving scheme in rotor field-orientated vector control is developed for induction motor drives. The energy-saving scheme minimizes copper and core losses in induction motors, which are equally applicable to induction generators. In efficiency optimization, an optimal stator angular velocity is uniquely obtained, and consequently, a corresponding optimal slip at any given rotor speed is determined. The challenge of determining a reference for rotor flux linkage that guarantees the minimal copper and core loss regime is overcome by developing a load torque observer loop. The torque observer is developed alongside a rotor speed observer for a sensorless speed operation. The observed mechanical torque is further used to enhance the outer-loop rotor speed control that generates an electromagnetic torque command used in building the reference for the inner-loop stator current control. The results obtained justified the effective operation of the torque and rotor speed observer, which consequently verified the effective minimal electrical loss regime at the optimal stator angular velocity and optimal rotor flux linkage. The results are further compared to results obtained from the equivalent induction machine drive on a finite-set model predictive control (FS-MPC) scheme with the same values of the optimal stator angular velocity and optimal rotor flux linkage. The developed efficiency-optimized vector control scheme gave lower ripples in developed electromagnetic torque and dampened overshoot better during step change in load torque.